Bedside mental status and outcome in elderly patients admitted for acute coronary syndromes. Issue 21 (29th May 2019) - Briet, Clément; Blanchart, Katrien; Lemaître, Adrien; Roux, Isabelle; Lavergne, Kelly; Rocamora, Amelia; Bignon, Mathieu; Ardouin, Pierre; Sabatier, Remi; Roule, Vincent; Beygui, Farzin
Abstract : Objective: We investigated whether mental status assessed by simple bedside tests in elderly patients admitted for acute coronary syndromes (ACS) was associated with higher risk of mortality. Methods: We used the data from a prospective, open, ongoing cohort of patients≥75 years old admitted for ACS to a tertiary centre. Cognitive impairment (CogI) was defined by delirium detected by the Confusion Assessment Method or an abnormal Mini Mental State Examination score. A Cox model adjusted on predefined correlates of mortality was used to assess the relationship between CogI and 1-year mortality. Results: Six-hundred consecutive patients with mental status assessment within 48 hours after admission were included. CogI was identified in 172 (29%) patients among whom 153 (25.5%) had an abnormal Mini Mental State Evaluation and 19 (3.2%) delirium. Death occurred in 49 (28.6%) patients with and 43 (10.5%) patients without CogI at 1 year. There was a significant association between CogI and 1-year mortality (adjusted-HR 2.4, 95% CI 1.53 to 3.62), p<0.001) independent of other covariables. CogI was also independently associated with higher rates of in-hospital bleeding and mortality as well as 3-month rates of all-cause, cardiovascular-related and heart failure-related rehospitalisation. Conclusions: CogI detected by simple bedside tests in patients≥75 admitted for ACS is associated with an increased risk of 1-year mortality and 3 month rehospitalisation independent of other correlates of poor outcome.